2009
DOI: 10.1152/ajplung.00020.2009
|View full text |Cite
|
Sign up to set email alerts
|

ASIC1 contributes to pulmonary vascular smooth muscle store-operated Ca2+entry

Abstract: Acid-sensing ion channels (ASIC) are voltage-insensitive, cationic channels that have recently been identified in vascular smooth muscle (VSM). It is possible that ASIC contribute to vascular reactivity via Na(+) and Ca(2+) conductance; however, their function in VSM is largely unknown. In pulmonary VSM, store-operated Ca(2+) entry (SOCE) plays a significant role in vasoregulatory mechanisms such as hypoxic pulmonary vasoconstriction and receptor-mediated arterial constriction. Therefore, we hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
61
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 65 publications
8
61
0
Order By: Relevance
“…However, ASIC1b (a splice variant of ASIC1) and ASIC3 are not permeable to Ca 2ϩ (7,17). As our results indicate the functional significance of ASIC1 and ASIC3 as downstream effectors of phenamil, we speculate that activation of the calcineurin-NFAT pathway by phenamil might be a result of sodium imbalance.…”
mentioning
confidence: 65%
See 3 more Smart Citations
“…However, ASIC1b (a splice variant of ASIC1) and ASIC3 are not permeable to Ca 2ϩ (7,17). As our results indicate the functional significance of ASIC1 and ASIC3 as downstream effectors of phenamil, we speculate that activation of the calcineurin-NFAT pathway by phenamil might be a result of sodium imbalance.…”
mentioning
confidence: 65%
“…ASICs are voltage-insensitive, pH-sensitive cationic channels permeable to Ca 2ϩ , Na ϩ , and K ϩ . Phenamil is known to inhibit ASICs more potently than other amiloride analogs (17). Four different ASIC genes have been identified, and ASIC proteins form homomeric or hetereomeric cation channels that are proton gated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ture, our laboratory has recently shown that ASIC1 is an important facilitator of G protein-coupled receptor signaling via store-operated Ca 2ϩ entry (SOCE) in pulmonary arterial smooth muscle cells (PASMC) (21,22). Furthermore, ASIC1-mediated Ca 2ϩ entry in PASMC appears to be an important constituent of both the active vasoconstrictor and vascular remodeling components of chronic hypoxic-induced pulmonary hypertension (21,31).…”
mentioning
confidence: 99%